Grey Correlation Analysis of the Relationship Between Port Logistics and Regional Economic Development in Tangshan City - Pengyu Dai (Journal of World Economy, 2023)
With the rapid development of the global economy, China has become one of the most important port logistics countries in the world. Port logistics not only promotes the vigorous development of port economy, but also promotes the development of regional economy to a great extent. Taking Tangshan Port as an example, this paper analyzes the correlation between the level of logistics development of Tangshan Port and the level of economic development of Tangshan City. Firstly, we analyze Tangshan Port from two dimensions: the current situation of port logistics development and the current situation of economic development, and secondly, we select relevant data from 2011 to 2020 to conduct a gray correlation analysis between the port throughput of Tangshan Port and various economic indicators of Tangshan City, and analyze the key factors affecting the development of Tangshan Port by calculating their correlation degrees and analyze the research results, based on which provides feasible suggestions for the port logistics development of Tangshan Port. The results show that the tertiary industry has the highest correlation with port logistics, followed by the total investment in fixed assets of the whole society. However, the economic data of total import and export trade has the lowest correlation with the development of port logistics, which indicates that there is a certain incongruity between the development of port logistics and import and export trade. Finally, some suggestions are put forward for the development of Tangshan port logistics, such as optimizing and upgrading the industrial structure, increasing the investment in logistics infrastructure construction, and promoting the coordinated development of import and export trade and port logistics, so as to promote the coordinated development of port logistics and economy.